2019
DOI: 10.3390/antiox9010017
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Rosa Canina Extracts and Gold Complex Favors Apoptosis of Caco-2 Cells by Increasing Oxidative Stress and Mitochondrial Dysfunction

Abstract: Given the alarming increase in colorectal cancer (CRC) worldwide, novel therapies are urgently needed. Plant-derived extracts have gained considerable interest in the last years due to their strong anticancer effect mediated by their unique bioactive compounds. Specifically, rosehips from Rosa canina have been successfully tested against several cancer models, including colon cancer. Moreover, gold derivatives are a promising alternative to the current platinum-based drugs commonly used in CRC chemotherapy due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…During the last few years, our research group has investigated the chemopreventive properties of extracts obtained from different plant matrices such as rosehips, fenugreek, pine bark, and artichoke waste on human colon cancer [ 3 , 25 , 26 , 27 ]. Though there have only been few publications on this subject, the anticarcinogenic potential of grape stem extracts has also been studied in different cell lines [ 13 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, our research group has investigated the chemopreventive properties of extracts obtained from different plant matrices such as rosehips, fenugreek, pine bark, and artichoke waste on human colon cancer [ 3 , 25 , 26 , 27 ]. Though there have only been few publications on this subject, the anticarcinogenic potential of grape stem extracts has also been studied in different cell lines [ 13 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…88 Recently, some authors assessed the extract of rosehip against different cancer cell lines, including colon, lung, prostate, cervix, liver, brain, and breast, suggesting its potential role in chemotherapy. 25,89 After treating these cancer cell lines with whole rose hip extract or purified fractions of its most important components, all studies have reported a noticeable decline in cell viability. These antioxidant properties may be responsible for their antiproliferative effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, tucum extract demonstrated a potent pro-oxidant effect in Caco-2 cells by increasing mitochondrial ROS production that was not observed in intestinal fibroblasts, thus indicating a cell type-specific action. The pro-oxidant effect of catechins is related to apoptosis induction in tumor cells, such as HL-60, HT-29 and RAW 264.7 due to interference with cellular signaling pathways or by increasing H 2 O 2 and hydroxyl radical production under experimental conditions (36)(37)(38)(39). ROS production is increased when Rosa canina is combined with a drug to treat colorectal cancer, but when Caco-2 cells treated with hydrogen peroxide are exposed to only Rosa canina's extract, ROS production decreases, showing an antioxidant effect (40,41).…”
Section: Discussionmentioning
confidence: 99%